The Role of Exclusive Breastfeeding, Low Birth Weight, and Immunization in Stunting Among Children Under Five - Yuliawati, Yuliawati; Anggraini, Yetti; Lestariningsih, Sri; Aghniya, Rofana; Yustiza, Non Rachmani (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2025)
Reducing stunting in children is the first of six Global Nutrition Targets for 2025 and serves as a key indicator in the Sustainable Development Goals (SDGs). Stunting is associated with increased risks of illness, mortality, and impaired motor and cognitive development in children. According to the 2022 Indonesian Nutrition Status Survey (SSGI), the prevalence of stunting in Lampung Province decreased to 15.2%, down from 18.5% in 2021. However, in Metro City, the prevalence increased from 7.29% (2021) to 10.4% (2022), with the highest rate recorded in the working area of Yosomulyo Health Center at 11%. This study aims to analyze the relationship between exclusive breastfeeding, history of low birth weight (LBW), and immunization status with the incidence of stunting in toddlers. This research is a quantitative study with a case-control analytic design. The population consisted of children aged 1–5 years who experienced stunting in the Yosomulyo Health Center working area between February and June 2024, totaling 84 children (11%). The sample consisted of 45 children in the case group and 90 children in the control group (a 1:2 ratio), selected using purposive sampling. Data were analyzed using the Chi-Square test with SPSS software after conducting a normality test. The analysis showed a significant relationship between exclusive breastfeeding, history of LBW, and immunization status with the incidence of stunting (p<0.001). Factors such as lack of exclusive breastfeeding, low birth weight, and incomplete immunization are significantly associated with the incidence of stunting. Early prevention of stunting can be achieved through proper pregnancy planning and regular antenatal care.